PETUNJUK RASULULLAH SAW TENTANG TUGAS DAN KEWAJIBAN PESERTA DIDIK - Abdul Wahab Syakhrani; Rahmatina Rahmatina; Rahmatul Rida; Rasmida Rasmida; Riska Reysa (EDUCATIONAL JOURNAL : General and Specific Research, 2022)
In the hadith Ahmad explained three important things that were ordered by the Prophet, namely, respecting people who are older than us, loving people who are younger than us, respecting and respecting people who are pious (teachers). In the Hadith of Ibn Majah it is explained that the key to success is Faith, faith is the foundation in doing righteous deeds because Allah will only accept the righteous deeds of those who believe in Him. While in another hadith of Ibn Majah no. 23 explained that in seeking knowledge, one must have a sincere intention to gain knowledge that is useful for oneself and for others and accompanied by morals and manners, because knowledge that is accompanied by morals will make the knowledge gained useful and of course also useful. . In the Hadith Tirmidhi no. 2417 explains to us not to stop studying, even to the end of our lives, besides that it also tells us that everything we do in this world, no matter how small, will be accounted for in the hereafter.